Podstawy metodologiczne segmentacji krajów i regionów z wykorzystaniem koncepcji łańcuchów celów i środków - Sobczak, Elżbieta (Methodological Bases for Segmentation of Countries and Regions Using Means-end-Chains Concept, 2006)
The objective of the hereby study is the proposal for macro- and mesoeconomic segmentation using means-end-chain concept. The basis for such segmentation becomes an assumption that competitive attributes of a country or a region are the means for an enterprise, which facilitate obtaining the desirable objectives, namely direct advantages and values. Configurations of attributes, advantages and values relations result in countries and regions diversifications, therefore they may become the basis for their classification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 171-179